The Adult Respiratory Distress Syndrome Cognitive Outcomes Study: long-term neuropsychological function in survivors of acute lung injury - Carlson, Catherine Gogela (BioMed Central, 2013)
EXPANDED ABSTRACT: CITATION: Mikkelsen ME, Christie JD, Lanken PN, Biester RC, Thompson BT, Bellamy SL, Localio AR, Demissie E, Hopkins RO, Angus DC: The adult respiratory distress syndrome cognitive outcomes study: long-term neuropsychological function in survivors of acute lung injury. Am J Respir Crit Care Med 2012, 185:1307-1315. BACKGROUND: Cognitive and psychiatric morbidity is common and potentially modifiable after acute lung injury (ALI). However, practical measures of neuropsychological function for use in multicenter trials are lacking. METHODS: OBJECTIVE: The objectives were to determine whether a validated telephone-based neuropsychological test battery is feasible in a multicenter trial and to determine the frequency and risk factors for long-term neuropsychological impairment. DESIGN: A prospective, multicenter cohort study of a subset of survivors from the Fluid and Catheter Treatment Trial (FACTT) was conducted. SETTING: The FACTT enrolled patients from 38 North American hospitals between June 2000 and October 2005. SUBJECTS: To be eligible for the ALI Cognitive Outcomes Study (ACOS), subjects had to be enrolled in the FACTT and the EA-PAC (Economic Assessment of the Pulmonary Artery Catheter) trial. The FACTT enrolled mechanically ventilated adults who met the American-European Consensus Conference criteria for ALI. INTERVENTION: In an adjunct study to the Acute Respiratory Distress Syndrome Clinical Trials Network Fluid and Catheter Treatment Trial, neuropsychological function at 2 and 12 months after hospital discharge was assessed. OUTCOMES: The primary outcome was the result of a validated telephone battery of standardized neuropsychological tests administered to consenting, English-speaking subjects at 2 and 12 months after hospital discharge. RESULTS: Of 406 eligible survivors, 261 patients were approached to participate and 213 consented. One hundred twenty-two subjects, including 102 subjects at 12 months, were tested at least once. Memory, verbal fluency, and executive function were impaired in 13% (12 of 92), 16% (15 of 96), and 49% (37 of 76) of long-term survivors, respectively. Long-term cognitive impairment was present in 41 (55%) of the 75 survivors who completed cognitive testing. Depression, post-traumatic stress disorder, and anxiety were present in 36% (37 of 102), 39% (40 of 102), and 62% (63 of 102) of long-term survivors, respectively. Enrollment in a conservative fluid management strategy (P <0.005) was associated with cognitive impairment, and lower partial pressure of arterial oxygen during the trial was associated with cognitive (P <0.02) and psychiatric (P <0.02) impairment. CONCLUSIONS: Neuropsychological function can be assessed by telephone in a multicenter trial. Long-term neuropsychological impairment is common in survivors of ALI. Hypoxemia is a risk factor for long-term neuropsychological impairment. A fluid management strategy is a potential risk factor for long-term cognitive impairment; however, given the select population studied and an unclear mechanism, this finding requires confirmation.